Pelatihan Manajemen Komunikasi Pemasaran Bagi Usaha Menengah Kecil Masyarakat Dalam Meningkatkan Pemberdayaan Ekonomi Masyarakat - Dwinarko; Ari Sulistyanto; Saeful Mujab (Yayasan Literasi Sains Indonesia, 2022)
This community service aims to provide knowledge and understanding through Marketing Communication Management training for Small Medium Enterprises (MSME) in Telagasari Village, Serangpanjang, Subang. The Covid-19 pandemic condition requires creativity and innovation in marketing MSME products. Methods Lectures, discussions, exercises and presentation of the results of the training for MSME managers in the village. The results of the service stated that the communication strategy required training and knowledge about the media and market opportunities for MSME products. Management planning and knowledge of competitors in improving product quality is supported by direct cash assistance (BLT) for MSME. Marketing communication strategy for MSME products in Tegalasari Village is needed, to consider several things related to marketing communication requiring training and business credit, to increase production and empower natural resources owned by continuous training and coaching. Increasing the number of MSMEs and production quality through HR training and product quality training.